Global marketing - Gillespie, Kate; Swan, K. Scott (New York, NY Routledge, an imprint of the Taylor & Francis Group, 2022)
"Strategic, comprehensive, and concise, the fifth edition of this popular textbook introduces students to the important concepts of global marketing today, and their managerial implications. Increasingly, marketing activities must be integrated at a global level. Yet, the enduring influence of culture requires marketers to adapt local strategies in light of cultural differences. Global Marketing takes a strategic approach, recognizing the need to address both the forces of globalization and those of localization. Key updates include: Extensive real-life examples and cases from developed and emerging markets, including Africa, Latin America and the Middle East; New topics such as digital distribution options, the participation of customers, and the rise of social media, including Twitter, Facebook and TikTok; Updated exploration of often overlooked topics, such as China's state-owned enterprises, the importance of diasporas as target markets, the threat of transnational criminal organizations to legitimate marketers, and new tensions among trading partners; A stronger recognition of the need for a growth mindset, value orientation, and innovation. Written in a student-friendly style, this fully updated new edition continues to be the textbook of choice for students of global marketing."--Provided by publisher.
First edition entitled: Global marketing : an interactive approach / Jean-Pierre Jeannet, H. David Hennessey. ©2004.
Includes bibliographical references and index.
Keywords: Export marketing; Export marketing -- Management